2019
DOI: 10.1016/j.cmet.2019.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Glycogenolysis Modulates Histone Acetylation in Human Non-Small Cell Lung Cancers

Abstract: Highlights d De novo synthesized glycogen accumulates in the nucleus of non-small cell lung cancers d Nuclear glycogen provides a carbon pool for histone acetylation d Nuclear glycogenolysis is dependent on translocation of glycogen phosphorylase d Glycogen phosphorylase translocation is regulated by the E3 ubiquitin ligase malin

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(90 citation statements)
references
References 105 publications
(120 reference statements)
2
86
0
2
Order By: Relevance
“…Depletion of malin impairs nuclear glycogenolysis by blocking nuclear translocation of PYG. The resulting accumulation of nuclear glycogen is reversed by re-introduction of malin in lung cancer cells which restores nuclear catabolism of glycogen, increases histone acetylation, and decreases growth of non-small-cell lung cancer xenografts in mice (51). This highlights the importance of glycogen beyond a cytoplasmic glucose reservoir, revealing this macromolecule as a key driver of compartmentalized tumor metabolism.…”
Section: Glycogen Driving Carcinogenesismentioning
confidence: 97%
See 2 more Smart Citations
“…Depletion of malin impairs nuclear glycogenolysis by blocking nuclear translocation of PYG. The resulting accumulation of nuclear glycogen is reversed by re-introduction of malin in lung cancer cells which restores nuclear catabolism of glycogen, increases histone acetylation, and decreases growth of non-small-cell lung cancer xenografts in mice (51). This highlights the importance of glycogen beyond a cytoplasmic glucose reservoir, revealing this macromolecule as a key driver of compartmentalized tumor metabolism.…”
Section: Glycogen Driving Carcinogenesismentioning
confidence: 97%
“…Interestingly, PYG via a mechanism involving the E3 ubiquitin ligase malin, can also translocate to the nucleus to drive nuclear glycogenolysis non-small cell in lung cancer, fueling compartmentalized pyruvate production and histone acetylation (51). Aberrant histone acetylation resulting in an altered epigenetic landscape is a hallmark of multiple cancers FIGURE 2 | (A) Impacts of glycogen on cells of the tumor microenvironment.…”
Section: Glycogen Driving Carcinogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Nuclear accumulation of glycogen was recently associated to epigenetic changes in gene expression and cancer (Sun et al, 2019). Moreover, liver cancer is an emerging feature of UCD (Koo et al, 2017;Wang et al, 2019;Wilson et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Lysine acetylation is a common posttranslational modification (PTM) regulating protein stability, subcellular localization, and function [17]. Acetylation of histone and nonhistone was reported to be involved in many diseases, including aging-associated chronic inflammation and insulin resistance [18], cancer [19][20][21], colitis [22], and Alzheimer's disease [23]. In previous work, we analyzed the lysine acetylproteome in three primary cervical cancer tissues and corresponding adjacent normal tissues by using the label-free proteomics approach and found that acetylation levels of CLIC1 at lysine 131 were significantly increased in tumor tissues.…”
Section: Introductionmentioning
confidence: 99%